Brassica-enriched wheat bread: Unraveling the impact of ontogeny and breadmaking on bioactive secondary plant metabolites of pak choi and kale. (15th October 2019) - Klopsch, Rebecca; Baldermann, Susanne; Hanschen, Franziska S.; Voss, Alexander; Rohn, Sascha; Schreiner, Monika; Neugart, Susanne
Highlights: Microgreens and leaves showed different secondary plant metabolite patterns. Nitriles were the main glucosinolate breakdown products found after breadmaking. Breadmaking caused pheophytin and pyropheophytin formation. Up to 84% of flavonoid glycosides could be recovered after breadmaking. Hydroxycinnamic acid derivative concentration increased up to 3-fold after breadmaking. Abstract: Consumption of Brassica vegetables is linked to health benefits, as they contain high concentrations of the following secondary plant metabolites (SPMs): glucosinolate breakdown products, carotenoids, chlorophylls, and phenolic compounds. Especially Brassica vegetables are consumed as microgreens (developed cotyledons). It was investigated how different ontogenetic stages (microgreens or leaves) of pak choi ( Brassica rapa subsp. chinensis ) and kale ( Brassica oleracea var. sabellica ) differ in their SPM concentration. The impact of breadmaking on SPMs in microgreens (7 days) and leaves (14 days) in pak choi and kale as a supplement in mixed wheat bread was assessed. In leaves, carotenoids, chlorophylls, and phenolic compounds were higher compared to those of microgreens. Breadmaking caused a decrease of SPMs. Chlorophyll degradation was observed, leading to pheophytin and pyropheophytin formation. In kale, sinapoylgentiobiose, a hydroxycinnamic acid derivative, concentration increased. Thus, leaves of Brassica species are suitable as natural ingredients for enhancing bioactive SPM concentrations in bread.